2015
DOI: 10.17265/2328-2150/2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

A Calcium Paradox in the Context of Neurotransmission

Abstract: Abstract:The hypothesis of the calcium paradox has its origin in experiments done in neurogenically stimulated rat and mouse vas deferentia. Some old studies reported that reduction of Ca 2+ entry by mild concentrations of verapamil, diltiazem or nifedipine elicited the surprising augmentation of vas deferens contractions. Recent reports have also found that nifedipine caused a paradoxical augmentation of the exocytotic release of catecholamine elicited by paired depolarising pulses in voltage-clamped bovine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…In addition, many results have shown that cAMP increases neurotransmitter release at many synapses in autonomic nervous system of vertebrate, including sympathetic neurons [7]. We recently showed that Ca 2+ /cAMP signalling interaction participates in the regulation of transmitters release from sympathetic neurons, and adrenal chromaffin cells [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, many results have shown that cAMP increases neurotransmitter release at many synapses in autonomic nervous system of vertebrate, including sympathetic neurons [7]. We recently showed that Ca 2+ /cAMP signalling interaction participates in the regulation of transmitters release from sympathetic neurons, and adrenal chromaffin cells [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, elevating [cAMP]c by handling Ca 2+ /cAMP signalling interaction could reduce neuronal death triggered by cytosolic Ca 2+ overload [8][9][10][11]. Then, the pharmacological handling of the Ca 2+ /cAMP signalling interaction produced by combination of the L-type CCBs prescribed in the antihypertensive therapy, and [cAMP] c-enhancer compounds prescribed in the anti-depressive therapy such as rolipram, could be a novel pharmacological strategy for enhancing neurotransmission in neurological, and psychiatric disorders, resulting of neurotransmitter release deficit, and neuronal death [8][9][10][11]. Figure 1 shows how the pharmacological modulation of the Ca 2+ /cAMP signalling by the Nobel laureate Erwin Neher [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations